2020
DOI: 10.1186/s12885-020-07216-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of prognostic tumor microenvironment-related genes in osteosarcoma patients

Abstract: Background Tumor microenvironment (TME) plays an important role in malignant tumors. Our study aimed to investigate the effect of the TME and related genes in osteosarcoma patients. Methods Gene expression profiles and clinical data of osteosarcoma patients were downloaded from the TARGET dataset. ESTIMATE algorithm was used to quantify the immune score. Then, the association between immune score and prognosis was studied. Afterward, a differential analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…The majority of these genes relate to occurrence or development of cancers and some could serve as the prognostic signature ( Liu et al, 2020 ; Wu et al, 2020 ). In osteosarcoma, several gene signatures related to energy metabolism, tumor microenvironment and immune system have been investigated ( Hong et al, 2020 ; Hu et al, 2020 ; Zhu et al, 2020 ). However, no hypoxia-associated prognostic signature has been established.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these genes relate to occurrence or development of cancers and some could serve as the prognostic signature ( Liu et al, 2020 ; Wu et al, 2020 ). In osteosarcoma, several gene signatures related to energy metabolism, tumor microenvironment and immune system have been investigated ( Hong et al, 2020 ; Hu et al, 2020 ; Zhu et al, 2020 ). However, no hypoxia-associated prognostic signature has been established.…”
Section: Introductionmentioning
confidence: 99%
“…As not all OS patients have greater benefit from immunotherapy, more immune microenvironment characteristics should be incorporated to instruct clinical treatment. Researchers have made great effort to reveal the role of tumor microenvironment and tumor microenvironment-related genes in OS by a series of bioinformatics methods [ 12 14 , 23 , 24 ]. In the present study, the ConsensusClusterPlus algorithm was utilized to identify the five reproducible immune subtypes in 87 OS patients from the TARGET database.…”
Section: Discussionmentioning
confidence: 99%
“…OS is no exception, and the tumor immune microenvironment is closely related to the prognosis of OS patients. Zhang et al first established the prognostic signature based on immune microenvironment-related genes for OS [ 14 ], and Hu et al performed comprehensive analysis of prognostic tumor microenvironment-related genes based on several validated genes [ 23 ]. Song et al identified a set of immune gene signature related to clinical response and was verified based on 45 OSA primary tumors [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many other studies that utilize a deconvolution method to study the tumor microenvironment of osteosarcoma. A number of them use the estimated immune infiltrations calculated using CIBERSORT and/or immune scores calculated using ESTIMATE to find immune-related genes that can predict the prognosis of osteosarcoma [ 22 25 ]. Another set of studies find genes with prognostic values by applying Cox model on survival data or performing differentially expressed genes analysis between two groups of interest, and then investigate the relationship between these genes and estimated immune infiltrates [ 26 30 ].…”
Section: Introductionmentioning
confidence: 99%